Comparison of Simplexa Flu A/B & RSV PCR with Cytospin-Immunofluorescence and Laboratory-Developed TaqMan PCR in Predominantly Adult Hospitalized Patients - Landry, Marie L. (American Society for Microbiology, 2014)
To compare Simplexa Flu A/B & RSV PCR with cytospin-immunofluorescence and laboratory-developed TaqMan PCR methods, 445 nasopharyngeal samples were tested. Of these, 199 were positive (46 for respiratory syncytial virus [RSV], 120 for influenza A, and 33 for influenza B) and 246 were negative. The direct fluorescent-antibody assay (DFA) detected 132 (66.3%) positive samples, Simplexa direct detected 162 (81.4%), Simplexa using extracts detected 177 (88.9%), and lab-developed TaqMan PCR reference methods detected 199 (100%). The specificities were 99.6%, 100%, 100%, and 100%, respectively. The two Simplexa methods were more sensitive than the DFA (P = 0.0001) but less sensitive than the TaqMan reverse transcriptase PCR (P = 0.0001).